Research progress and prospects of virus-like particles in tumor therapy - LIU Chun, CHEN Guoxin, LI Mengtian, ZHAO Yu, MA Zhongren, ZHANG Haixia (Zhongguo aizheng zazhi, 2025)
Virus-like particles (VLPs) are hollow nanoparticles composed of one or several virus structural proteins, which have a morphological structure similar to natural viruses but do not contain any genetic material. Due to the excellent innate immunogenicity and safety of VLPs, they are often used in the development of tumor vaccines. In addition, compared with traditional drug delivery vectors, VLPs have better biocompatibility and strong targeting ability, making them highly valued in the delivery of anti-tumor drugs. In recent years, the efficient delivery of gene editing tools using VLPs has provided new possibilities for tumor treatment. VLPs can inhibit tumor growth and spread through various mechanisms, such as activating immune responses to suppress tumor growth, stimulating the body's immune system, promoting the expression of tumor associated antigens, and enhancing the body's ability to recognize and clear tumor cells. These studies not only broaden the application scope of VLPs in the field of anti-tumor therapy, but also provide a broader prospect for future research and application. This article reviewed the research progress of VLPs derived from different viruses in preventive or therapeutic vaccines and drug delivery carriers, and explored new development strategies.